Wear Resistance of Bronze-Matrix Samples of Diamond Tubular Drills with Ultrafine Diamond and Molybdenum Powder Reinforcement - Umansky, V.P.; Brodnikovsky, N.P.; Bashchenko, O.A.; Kulakov, A.S. (Powder metallurgy and metal ceramics, 2020)
The paper examines the abrasive wear rate of samples produced by vacuum impregnation of ultrafine diamond (ASM 1/0) and molybdenum powders with tin bronze. The tests were performed using a SiC-based abrasive wheel in the presence of cooling water. The introduction of and increase in the ultrafine diamond powder in the samples substantially decrease their wear rate (by a factor of 78). The hardness of the samples first increases when diamond powder content rises to 5 wt.% and then decreases when ASM 1/0 content further rises to 11 wt.% because of small porosity that appears in the samples. The use of a bronze matrix containing more than 15 wt.% Sn does not decrease the wear rate of the test samples and, hence, of the associated diamond tools, in spite of increase in their hardness.